Impact of Temperature and Relative Humidity on Development of Aspergillus flavus Rot of Mango Fruit - Ashok M. Chavan, D.P. Gadgile (Recent Research in Science and Technology, 2010)
Effect of temperature and relative humidity on severity of disease, spore germination, Cellulase and pectinase enzyme activity of Aspergillus flavus rot was studied. It was found that low temperature and low relative humidity inhibits severity of disease, spore germination, cellulase and pectinase enzyme activity of A. flavus.